The doctrinal and interpretative emphases of the Bezan readings of the Gospel - Weinhauer, William Gillette (New York City : General Theological Seminary, 1969)
Anyone who teaches a course of study in the New Testament, using the Greek text and taking note of the variants occurring in a critical apparatus, must sooner or later wonder about the possibility of an overall theological pattern to the variant readings of different manuscripts. The question may be put this way: Does manuscript "so-and-so" with its assorted and manifold variants reflect a pattern of a particular theological interest, or does it simply contain haphazard, random collection--from many sources and for many reasons--of different readings which defy such systematization? Most teachers and students probably rest content with an answer which is little more than a suspicion or feeling, to be deferred to some leisured moment for further investigation or thought. Some, however, are beginning to ask the question with greater urgency and to seek an answer by more exhaustive searching.
Submitted in partial fulfillment of the requirements for the Degree of Doctor of Theology in the General Theological Seminary, New York City
Dissertation (D.Theo.)-General Theological Seminary